FORMULATING THE EVALUATION MODEL OF EDUCATIONAL MUSIC VIDEO FOR CHILDREN’S LEARNING (EMV4CL) (Journal of Creative Industry and Sustainable Culture, 2024)
This study, part of a Ph.D. thesis, explores the role of Educational Music Videos (EMVs) in enhancing children's learning within the framework of Video-Based Learning (VBL). EMVs, which adapt the traditional music video format by embedding educational content through singing narration, offer a novel approach to creating engaging and enjoyable learning experiences for young learners. However, the educational potential of EMVs has not been fully realized due to the absence of specific guidelines for evaluating their appropriateness for children's learning. To address this gap, the study develops the Evaluation Model of Educational Music Videos for Children’s Learning (EMV4CL). The model is grounded in Design Research methodology and identifies five critical components necessary for the effective evaluation of EMVs: video content, audio-visual learning concepts, video presentation style, edutainment features, and interactive activities. Each component was meticulously designed to capture the unique characteristics that make EMVs suitable for educational purposes. The EMV4CL model was subsequently validated by 11 academic experts, who unanimously endorsed its relevance and applicability in assessing the educational quality of music videos for children. The findings of this study highlight the EMV4CL as a significant contribution to the field, providing a structured and comprehensive tool that educators and developers can use to produce and evaluate high-quality educational music videos. This research advances the understanding of how music videos can be effectively utilized to support and enhance children's learning.